A Contribution From the American-Indonesian Scholarship Program Alumni Association to Indonesia: The ’Local Heroes for Forest Protection’ Initiative in Southeast Sulawesi, West Papua, and East Nusa Tenggara - Hermudananto, Hermudananto; Alfian, Alfian; Lapau, Fitri; Rahayu, Kadek Ridoi; Sukoyo, Kuntari Sri; Zulkifli, Miranti Triana; Rajahasta, Patih; Murianty, Riana; Hermawan, Rudi; Landa, Silvia Anastasia (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2025)
To minimize forestry sector greenhouse gas emissions by 2030, Indonesia needs stakeholder participation, especially youth. The AmericanIndonesian Scholarship Program Alumni Association (ALPHA-I) initiated the "Local Heroes for Forest Protection" program to include local adolescents in climate action. During 2023-2024, 149 direct participants from three provinces (Sulawesi Tenggara, Papua Barat, and Nusa Tenggara Timur) contributed to the conservation of approximately 12.5 hectares of forest, surpassing our target area, by planting indigenous trees and indirectly impacting around 4,500 individuals through both online and on-site campaigns. The program encompassed capacity-building training, sustainability seminars, field activities, and displays via a talk-show festival on climate change, which garnered favorable comments. Despite the SWOT analysis indicating that all three regions have analogous obstacles and opportunities in program implementation, they effectively formulated action plans for forthcoming activities. Our program is anticipated to persist for three years, broadening its effects to more regions while fostering partnerships with various local and national organizations.